Evolutionary computation: Main paradigms and current directions - Michalewicz, Zbigniew; Michalewicz, Maciej (Zielona Góra: Uniwersytet Zielonogórski)
Evolutionary computation techniques, which are based on a powerful principle of evolution: survival of the fittest, constitute an interesting category of heuristic search. Evolutionary computation techniques are stochastic algorithms whose search methods model some natural phenomena: genetic inheritance and Darwinian strife for survival.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka